Analisis Sistem Manufaktur Mesin Multifungsi (Pencuci, Perajang dan Penepung) Empon-Empon - Desmas Arifianto Patriawan; Bambang Setyono; Deddy Wahyu Pratomo (Institut Teknologi Adhi Tama Surabaya, 2022)
In Indonesia, spices have been widely used in the industries of food, drink, cosmetics, coloring substance, and essential oil. A biopharmaceutical industry refers to an industry producing medicine, cosmetics, and health products made of spices. To support the needs of biopharmaceutical industry, a multifunctional machine has been developed continuously to reach great effectiveness. A multifunctional machine (washer, slicer, and miller) has three main functions i.e. washing, slicing, and milling spices. To analyze the manufacturing system of this multifunctional machine, the researcher employed standard time in calculating production cost, production rate, production capacity, and Break Even Point of product that has been developed. As a result, this research obtained time of production (Tp) = 54.44 hours/batch and rate of production IDR =3.05 units/hour. Within the condition of effective working hours for 8 hours/shift, the production capacity (Pc) earned 1 unit/month. Furthermore, the calculation yielded Manufacturing Lead Time (MLT) = 44.80 hours, BEP (Q) = 2 units, while BEP (IDR) = 9,583,068.6/month. Accordingly, the profit got IDR12,810,083/month.Keywords: Biopharmaceutical industry, multifunctional machine, manufacture